2002
DOI: 10.1002/jnr.10529
|View full text |Cite
|
Sign up to set email alerts
|

Monoaminergic control of vasopressin and VIP expression in the mouse suprachiasmatic nucleus

Abstract: We studied the effects of serotonin and noradrenaline on the expression of arginine-vasopressin (AVP) and vasoactive intestinal peptide (VIP) in the suprachiasmatic nucleus (SCN). We used transgenic Tg8 mice knockout for the MAO-A (monoamine oxidase A) gene, which are characterized by increased amounts of serotonin and noradrenaline in brain compared to wild-type mice (C3H). The MAO-A deficiency caused an increase in AVP and VIP expression (determined by immunohistochemistry, enzyme immunoassay, and in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…Semba et al (14) demonstrated that NA levels in rat SCN are high during periods of light and low during periods of darkness, pointing to circadian oscillation of NA levels. Moreover, NA might modulate SCN circadian rhythms by regulating expression of arginine-vasopressin and vasoactive intestinal peptides, substances hypothesized to participate in control of circadian rhythms (15). In addition to the SCN, reports also have demonstrated that NA generates circadian-clock oscillation in peripheral organs and cells (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Semba et al (14) demonstrated that NA levels in rat SCN are high during periods of light and low during periods of darkness, pointing to circadian oscillation of NA levels. Moreover, NA might modulate SCN circadian rhythms by regulating expression of arginine-vasopressin and vasoactive intestinal peptides, substances hypothesized to participate in control of circadian rhythms (15). In addition to the SCN, reports also have demonstrated that NA generates circadian-clock oscillation in peripheral organs and cells (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In Tg8 mice, MAO‐A deficiency is correlated with an increase in brain 5‐HT and NA concentrations that is particularly marked in the SCN (Vacher et al ., 2003). Suprachiasmatic levels of AVP peptide and mRNA were higher in Tg8 than in C3H mice, suggesting a positive effect of monoamines on AVP expression at P11 in this nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, injections of pCPA to Tg8 mice induced an increase in AVP contents in the SCN, indicating a negative control of 5‐HT on AVP expression at P11. In the light of our previous data, which suggest a stimulatory effect of 5‐HT on AVP expression in the adult mouse SCN (Vacher et al ., 2003; Fig. 4A), this result reveals a differential sensitivity of AVP neurons to monoamines with age in mouse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations